Effects of tannic acid interfacial absorption on the physicochemical stability of algal oil-loaded emulsions and inhibition of fishy off-flavor. (1st March 2023) - Wang, Xinshuo; Wang, Xingwei; Xia, Shuqin; Yu, Jingyang; John Swing, Caleb
Graphical abstract: Highlights: The fortification of tannic acid prevented the fishy smell of algae oil emulsions. The proportion of tannic acid located on the interface was more than 90%. OSA starch - tannic acid complexes stabilized emulsions had good oxidative stability. The interaction forces were hydrogen bonding and van der Waals forces in complexes. Abstract: In the present study, the inhibition of fishy off-flavor and destabilization in algae oil-loaded emulsions by tannic acid (TA) adsorption on octenyl succinic anhydride (OSA) starch interfaces were investigated. The changes of typical fishy off-flavor components in the emulsion, physiochemical stability, and interaction between TA and OSA starch were analyzed. The TA fortification significantly prevented the production of fishy smell-related volatile components such as heptanal and (E, E)-3, 5-octadiene-2-one. The proportion of TA on the interface was more than 90 %, forming an interfacial film with the antioxidant function. The emulsions stabilized by OSA starch-TA complexes had better oxidative and physical stability. The isothermal titration calorimetry suggested that the interaction between OSA starch and TA included hydrogen bonding and van der Waals forces (Δ G = -13.272 kJ·mol −1 ·K −1, Δ H = -1.302 × 10 3 kJ·mol −1, Δ S = -4.326 kJ·mol −1 ·K −1 ). Altogether, these results provided application guidance for developing starch-based oil-in-water emulsion systems with antioxidant properties.